A study on the robustness of a multirate predictive controller - Li, Chang En. (2008)
Predictive control methods have been widely accepted by the process industries. On the other hand, multirate control schemes also received considerable research interests because of the rapid development in the technology of digital computers and micro-processors. As a combination of these two trends, the research of multirate predictive controllers emerged as a new area in control theory and application.